Measuring Business Process Maturity Level on CRM - Customer Care, Using Framework eTOM and IT-IL, Based on Staff Perception at PT. X - Lihardo Ranjaliba Saragih; Gendut Suprayitno; Dahmir Dahlan (Pusat Penelitian Informatika - LIPI, 2014)
Nowadays a Telecom Company doing a business model transformation through managed services. This term as form of outsourcing managed services for telecom companies are very attached to the cutting-edge technology that is capital intensive, therefore it needs a different outsourcing approach in order to remind the competitiveness, not just a simple outsourcing employee in generally. This approach changes the employees outsourcing paradigm in the global telecommunications industry.Company realizes that managed service are complicated to be defined, even more complicate when its executed, thus necessary to have a good business processes maturity level measurement. This study is conducted to examine the business processes maturity level that build managed services leads business model rearrangement in companies.Researchers use eTOM and IT-IL framework for business unit’s maturity level measurement at “Customer Relationship Management (CRM) - Customer Care”, which will implement outsourcing through managed service. The study results is the factors/aspects identification that related to the potential outsourced managed services, restructuring advice of manage service Governance according to the existing business processes maturity level, in the end able to provide appropriate policy recommendations as well.